2010
DOI: 10.1039/b924822f
|View full text |Cite
|
Sign up to set email alerts
|

Laser spectroscopic study on (dibenzo-24-crown-8-ether)–water and –methanol complexes in supersonic jets

Abstract: The conformation and complex formation with guest molecules have been investigated for jet-cooled dibenzo-24-crown-8-ether (DB24C8) by laser induced fluorescence (LIF), UV-UV hole-burning (UV-UV HB), and IR-UV double-resonance (IR-UV DR) spectroscopy. The results are compared with the results of dibenzo-18-crown-6-ether (DB18C6) and analyzed by density functional theory (DFT) calculations at the B3LYP/6-31+G* level. Five conformers are identified for DB24C8 under jet-cooled conditions, and the structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…We investigate how the structural flexibility affects the dynamics of the inclusion process at the microscopic level. The doublet structure is also observed in DB24C8 [49] but not in B18C6, [46] and is attributed to an exciton splitting [49] due to the interaction of the two benzene chromophores. [47] The UV-UV HB spectra obtained by monitoring bands m1, m2, a, and c-f in Figure 1 b-h indicate that each of these bands can be assigned to the band origin of different species.…”
Section: Inclusion Complexes Of Benzene-substituted Crown Ethers Withmentioning
confidence: 87%
See 2 more Smart Citations
“…We investigate how the structural flexibility affects the dynamics of the inclusion process at the microscopic level. The doublet structure is also observed in DB24C8 [49] but not in B18C6, [46] and is attributed to an exciton splitting [49] due to the interaction of the two benzene chromophores. [47] The UV-UV HB spectra obtained by monitoring bands m1, m2, a, and c-f in Figure 1 b-h indicate that each of these bands can be assigned to the band origin of different species.…”
Section: Inclusion Complexes Of Benzene-substituted Crown Ethers Withmentioning
confidence: 87%
“…Recently, it has been demonstrated that the laser spectroscopic study of cold gas-phase CEs and their complexes, not only for ionic species [32][33][34][35][36][37][38][39][40][41][42][43] but also the neutral species, [44][45][46][47][48][49][50][51][52] can provide A laser spectroscopic study on the structure and dynamics of cold host-guest inclusion complexes of crown ethers (CEs) with various neutral and ionic species in the gas phase is presented. The complexes with neutral guest species are formed by using supersonic free jets, and those with ionic species are generated with electrospray ionization combined with a cold 22-pole ion trap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7a), and DB24C8ÁH + (Fig. 21 The S 1 -S 0 electronic transition of DB24C8ÁH + is roughly 800 cm À1 blueshifted with respect to that of neutral DB24C8. The spectrum of dBAMÁH + ÁDB24C8 shows broad structures with a band origin at B36 350 cm À1 .…”
Section: Complexes Of Dbamáh + With 18c6 and 24c8mentioning
confidence: 94%
“…[18][19][20][21][22][23][24][25][26][27] The cold gas phase complexes are generated either by the supersonic expansion technique for neutral complexes [18][19][20][21][22][23][24] or by the electrospray ionization (ESI)/cold ion-trap method for ionic complexes. [18][19][20][21][22][23][24][25][26][27] The cold gas phase complexes are generated either by the supersonic expansion technique for neutral complexes [18][19][20][21][22][23][24] or by the electrospray ionization (ESI)/cold ion-trap method for ionic complexes.…”
Section: Introductionmentioning
confidence: 99%